A new simple method for point contact Andreev reflection (PCAR) using a self-aligned atomic filament in transition-metal oxides1. Issue 18 (14th May 2015) - Hwang, Inrok; Lee, Keundong; Jin, Hyunwoo; Choi, Sunhwa; Jung, Eunok; Park, Bae Ho; Lee, Suyoun
<x xml:space="preserve">Abstract</x> Point contact Andreev reflection (PCAR) has become a standard method for measuring the spin polarization (P) of spintronic materials, but it is still challenging to achieve a clean point contact between a superconductor (SC) and a metal (N) for implementing PCAR.